Analysis of risk factors related to the progression rate of hemifacial spasm - Xu, Fei; Gu, Pengju; Yuan, Huan; Jiang, Li; Xie, Yanfeng; Shi, Quanhong; Zhan, Yan (Frontiers in Neurology, 2024)
Introduction Although there have been many researches on the etiology and risk factors with the onset of hemifacial spasm, researches on the risk factors related to progression rate are limited. This study aims to analyze the risk factors related to the progression rate of hemifacial spasm. Methods The study enrolled 142 patients who underwent microvascular decompression for hemifacial spasm. Based on the duration and severity of symptoms, patients were classified into rapid progression group and slow progression group. To analyze risk factors, univariate and multivariate logistic regression analyses were conducted. Of 142 patients with hemifacial spasm, 90(63.3%) were classified as rapid progression group, 52(36.7%) were classified as slow progression group. Results In the univariate analysis, there were significant statistical differences between the two groups in terms of age of onset (P = 0.021), facial nerve angle (P < 0.01), hypertension (P = 0.01), presence of APOE ε4 expression (P < 0.01) and different degrees of brainstem compression in the Root Entry Zone (P < 0.01). In the multivariable analyses, there were significant statistical differences between the two groups in terms of age of symptom onset (P < 0.01 OR = 6.591), APOE ε4 (P < 0.01 OR = 5.691), brainstem compression (P = 0.006 OR = 5.620), and facial nerve angle (P < 0.01 OR = 5.758). Furthermore, we found no significant correlation between the severity of facial spasms and the progression rate of the disease (t = 2.47, P = 0.12>0.05). Conclusion According to our study, patients with facial nerve angle ≤ 96.5°, severer compression of the brainstem by offending vessels, an onset age > 45 years and positive expression of APOE ε4, may experience faster progression of hemifacial spasm.